PERAN MOTIVASI BELANJA MEMEDIASI PENGARUH EWOM TERHADAP NIAT BELI PRODUK MELALUI MEDIA SOSIAL TIKTOK - Jayanthi, Ni Kadek Zilda Dwi; Sri Suprapti, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.03.TAHUN.2024, 2024)
The development of information and communication technology marked by the emergence of the internet has had an impact on various aspects of life. One of them is having an impact on the way consumers shop, which was originally done offline, now many are switching to online. The emergence of various social media has caused marketers to use these media to communicate their products to consumers and for consumers as a means of expressing their opinions about the products purchased. This study aims to determine the effect of electronic word of mouth, shopping motivation on purchase intentions on social media TikTok, and to determine whether shopping motivation is a mediating variable. This study used a purposive sampling technique with a sample of 100 respondents who live in Denpasar City. The data obtained were analyzed using path analysis and Sobel test. The results of the study found that electronic word of mouth has a positive and significant effect on shopping motivation, shopping motivation has a positive and significant effect on purchase intentions, electronic word of mouth has a positive and significant effect on purchase intentions, and shopping motivation can mediate the effect of electronic word of mouth on purchase intentions. The implication of this research is that eWOM which is conveyed very well through TikTok media is able to cause users to have high motivation to shop and generate a strong intention to buy products advertised through TikTok.